2015
DOI: 10.1007/s00011-015-0859-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of NOD1/CARD4 and NOD2/CARD15 genetic variations in lung cancer risk

Abstract: According to our data, the rs5743336 variant of the NOD1/CARD4 gene may influence the diagnosis and treatment of lung cancer, whereas the rs2066847 variant of the NOD2/CARD15 gene is not associated with lung cancer risk in the Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…NOD1 (also known as NOD1/CARD4 or NLRC1) is found on chromosome 7p14‐15 and expressed in both epithelial and myeloid‐derived cells . The rs5743336 variation of NOD1 gene results from the G to A transition at position 796 in exon 3 (peptide change: E266K) …”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…NOD1 (also known as NOD1/CARD4 or NLRC1) is found on chromosome 7p14‐15 and expressed in both epithelial and myeloid‐derived cells . The rs5743336 variation of NOD1 gene results from the G to A transition at position 796 in exon 3 (peptide change: E266K) …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…NOD2 (also known as NOD2/CARD15 or NLRC2) is found on chromosome 16q12 and is primarily expressed by myeloid cells . The rs2066847 variant of NOD2 gene is a frameshift mutation (p.Leu1007fsX1008) resulting from an insertion of a cytosine at nucleotide position 3020 (3020insC).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Nucleotide-binding oligomerization domain 1 (NOD1) receptor, is a relatively recently described cytosolic PRR known to execute important functions in the immune system (Girardin et al, 2001, Ogura et al, 2001) by recognizing a wide range of microbes bearing the specific meso-diaminopimelic acid (meso-DAP) moiety and mediating the corresponding inflammatory response to these infectious agents (Carneiro et al, 2004). Not only is NOD1 important in host defense and autoimmune diseases, but recently, it has also been implicated in tumorigenesis for a number of cancers, including gastric cancer (Wang et al, 2012), head and neck carcinomas (Millrud et al, 2013), oral squamous cell cancer (Wang et al, 2014), prostate adenocarcinoma (Kang et al, 2012), and lung cancer (Ozbayer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tatsumi et al reported that BNIP2 negatively regulates AKT prosurvival pathway through BMCC1 and induces apoptosis in human cancer cells 36. Polymorphisms of this gene were associated with various cancers, including breast cancer 37. BAG1 is a multifunctional protein with numerous targets that is implicated in the regulation of cell growth and apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%